2020
DOI: 10.3897/herpetozoa.33.e48541
|View full text |Cite
|
Sign up to set email alerts
|

First study of sea turtle strandings in Algeria (western Mediterranean) and associated threats: 2016–2017

Abstract: Between December 2015 and December 2017 a total of 63 sea turtles were recorded as being stranded along the Algerian coast. The loggerhead sea turtle Caretta caretta was the most commonly stranded species (n = 44) (69.8%), followed by the leatherback Dermochelys coriacea (n = 18) (28.6%) and the green turtle Chelonia mydas (n = 1). There was a slight dominance of the adult size class for stranded loggerhead turtles, while, for the leatherback, late juveniles and adults prevailed. Most loggerhead turtles strand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…For this reason, any potential increase in the bluefin tuna quotas for the longline fleet in the western Mediterranean should be accompanied by measures aimed at reducing loggerhead turtle bycatch, such as avoiding the use of squid as bait and deploying hooks deeper than 25 m (Swimmer et al, 2017), which must be considered by all countries involved in the fishery. Furthermore, bycatch in other fisheries should also be reduced, as adult loggerhead turtles are often captured incidentally by artisanal fisheries operating off Morocco and Algeria (Belmahi et al, 2020; Mghili et al, 2023). Considering that regional population estimates for the Mediterranean population are likely to be considerably overestimated (Rees et al, 2020), the conservation of any adult loggerhead turtle is more important than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, any potential increase in the bluefin tuna quotas for the longline fleet in the western Mediterranean should be accompanied by measures aimed at reducing loggerhead turtle bycatch, such as avoiding the use of squid as bait and deploying hooks deeper than 25 m (Swimmer et al, 2017), which must be considered by all countries involved in the fishery. Furthermore, bycatch in other fisheries should also be reduced, as adult loggerhead turtles are often captured incidentally by artisanal fisheries operating off Morocco and Algeria (Belmahi et al, 2020; Mghili et al, 2023). Considering that regional population estimates for the Mediterranean population are likely to be considerably overestimated (Rees et al, 2020), the conservation of any adult loggerhead turtle is more important than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of sea turtles along the Algerian coast is regularly reported, with many beachings, of which 70% are the loggerhead turtle, Caretta caretta (Linnaeus, 1758) and 30% of the leatherback Sea turtle, Dermochelys coriacea (Vandelli, 1761) ( Bennounas and Bennounas 2020 , Belmahi et al 2020 ). The green Sea turtle Chelonia mydas (Linnaeus, 1758) is the rarest species, having been recorded only once since 2003 (Bennounas and Tifoura 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The number of stranded sea turtles•km −1 , as well as the absolute numbers of strandings during the four years, clearly confirmed that the area south of the Po River delta is the most impacted in Italy (Casale et al ., 2010) and perhaps in the whole Mediterranean Sea (Tomás et al ., 2008; Bellido et al ., 2010; Corsini-Foka et al ., 2013; Türkozan et al ., 2013; Belmahi et al ., 2020; Hama et al ., 2020; Dimitriadis et al ., 2022). Although the extension of the monitored area appeared to be much greater, only Karaa et al .…”
Section: Discussionmentioning
confidence: 99%